2014
DOI: 10.5267/j.msl.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the level of customer oriented in an excellence business organization through EFQM method

Abstract: Today, many business organizations have replaced product oriented strategies with customer oriented strategies and try to improve the level of their products and services to reach customer satisfaction. Excellent organizations pay especial attention to their customers and always try to do their best to have loyal customers. The purpose of this paper is to investigate the level of customer oriented in an excellence business organization through European Foundation of Quality Management (EFQM) method for one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They concluded that it was difficult to determine a perfect match between a company and a performance measurement framework. Hosseini and Aalikhani (2014) investigated the level of customer oriented in an excellence business organization through EFQM method for one of the biggest Iranian banks in city of Tehran, Iran. Abbasi and Farhangi (2013) used EFQM method for broadcasting firm in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it was difficult to determine a perfect match between a company and a performance measurement framework. Hosseini and Aalikhani (2014) investigated the level of customer oriented in an excellence business organization through EFQM method for one of the biggest Iranian banks in city of Tehran, Iran. Abbasi and Farhangi (2013) used EFQM method for broadcasting firm in Iran.…”
Section: Introductionmentioning
confidence: 99%